Proliferative vitreoretinopathy in human immunodeficiency virus-infected patients in the era of highly active antiretroviral therapy - Kunavisarut P. (2014)
Purpose: To assess the prevalence of proliferative vitreoretinopathy (PVR) and prognosis of cytomegalovirus (CMV) retinitisrelated retinal detachment (RD) surgery in the era of highly active antiretroviral therapy (HAART). Design: Retrospective interventional cohort study. Methods: Thirty-five human immunodeficiency virus (HIV)-positive patients with CMV retinitisrelated RD who underwent surgical repair were assessed for PVR, CD4-positive T cell counts, and use of HAART. Main outcome measures included anatomic and functional outcomes of RD surgery as well as the presence of PVR and CD4-positive T cell counts. Results: PVR was present in 10 of 35 patients (29%) at the time of the first surgery. The presence of PVR was associated with worse preoperative and postoperative visual acuity (P = .017 and P = .009, respectively), with the CD4-positive T cell counts above 200 cells/μL (P = .054), and with a longer interval between the diagnosis of RD and surgery (P = .025). The odds ratio for development of PVR in patients with CD4-positive T cells above 200 cells/μL was 11.3 (95% confidence interval 1.01-125). PVR was not associated with age, gender, or duration of HIV infection. Anatomic reattachment was obtained in 31 patients (89%), though the functional outcomes were limited. The central location of CMV retinitis was associated with postoperative visual acuity (VA) of less than 0.1 (P = .000). Postoperative logMAR VA was associated with preoperative logMAR VA (P < .001) and development of PVR (P = .009). Conclusion: PVR was present in 29% of CMV retinitisrelated RD and was associated with higher CD4-positive T cell counts and longer interval between the diagnosis of RD and surgery. © 2010 Elsevier Inc. All Rights Reserved.